Holocene sea ice variability driven by wind and polynya efficiency in the Ross Sea. Issue 1 (December 2017) - Mezgec, K.; Stenni, B.; Crosta, X.; Masson-Delmotte, V.; Baroni, C.; Braida, M.; Ciardini, V.; Colizza, E.; Melis, R.; Salvatore, M.; Severi, M.; Scarchilli, C.; et al.
Abstract The causes of the recent increase in Antarctic sea ice extent, characterised by large regional contrasts and decadal variations, remain unclear. In the Ross Sea, where such a sea ice increase is reported, 50% of the sea ice is produced within wind-sustained latent-heat polynyas. Combining information from marine diatom records and sea salt sodium and water isotope ice core records, we here document contrasting patterns in sea ice variations between coastal and open sea areas in Western Ross Sea over the current interglacial period. Since about 3600 years before present, an increase in the efficiency of regional latent-heat polynyas resulted in more coastal sea ice, while sea ice extent decreased overall. These past changes coincide with remarkable optima or minima in the abundances of penguins, silverfish and seal remains, confirming the high sensitivity of marine ecosystems to environmental and especially coastal sea ice conditions. Strong regional heterogeneity prevents thorough understanding of the recent increase in Antarctic sea ice. Here, analysis of marine and ice cores in the Western Ross Sea shows that late Holocene contrasting sea ice patterns between open and coastal areas are related to katabatic winds and polynya efficiency.